Effects of Project-Based Learning Strategy on Student Metacognitive Skill to Learning Biology - Mawarti Endah Pratiwi (Pancaran Pendidikan, 2018)
Learning of Science in Indonesia especially for Biology nowadays drives students to find out their own concept and do their own experiment so they can understand well about their own concept and learning much for the environment around them. This learning can improve student metacognitive skill that student awareness about thinking their self thinking. The learning strategy that can improve these competences is Project-Based Learning. This experiment is going to do to understand about the effect of this strategy on student metacognitive skill. The research is going on SMAN 7 and SMAN Gondanglegi Malang in second semester for 2009/2010. Students in 2 classes each school as a sample of population of this research. This is quasi experiment that use non equivalent group design and anacova nonfaktorial for analyze the results. Results of this research show that project-based learning doesn’t give different effect on students metacognitive skill even if compared by control class that learning by multistrategy. Students metacognitive skill increase to 3,2% whether students in control class increase to 5,5%. This result show us that PBL strategy must be applicate on certain condition. Project-based learning base on this research can improve not only students retention achievement, it also predict can improve students skill process, confidence, and their attitude. Based on this situation so it is important to do the next research that assay the project-based learning on improving students skill process and their attitude to the environment.